Skills-Displacing Technological Change and Its Impact on Jobs: Challenging Technological Alarmism? - Seamus McGuinness; Konstantinos Pouliakas; Paul Redmond (Institute of Labor Economics (IZA), 2019)
We use data from a new international dataset - the European Skills and Jobs Survey - to create a unique measure of skills-displacing technological change (SDT), defined as technological change that may render workers' skills obsolete. We find that 16 percent of adult workers in the EU are impacted by SDT, with significant variance across countries, ranging from a high of 28 percent in Estonia, to below seven percent in Bulgaria. Despite claims that technological change contributes to the deskilling of jobs, we present evidence that SDT is associated with dynamic upskilling of workers. The paper also presents the first direct micro-evidence of the reinstatement effect of automating technology, namely a positive contribution of automation to the task content and skills complexity of the jobs of incumbent workers. Despite the recent focus on the polarising impact of automation and associated reskilling needs of lower-skilled individuals, our evidence also draws attention to the fact that SDT predominantly affects higher-skilled workers, reinforcing inequalities in upskilling opportunities within workplaces. Workers affected by SDT also experience greater job insecurity.
Keywords: J24; O33; O31; 330; technological change; automation; skills; tasks; skill mismatch; skills obsolescence